DIGITALISASI PELAPORAN DAN PEMERIKSAAN GROUND SUPPORT EQUIPMENT (GSE) DI BLU KANTOR UPBU KELAS I AJI PANGERAN TUMENGGUNG PRANOTO SAMARINDA - Septio Caesar Pangestu; Elfi Amir; Dian Anggraini Purwaningtyas (Journal of Social and Economics Research, 2025)
The advancement of information technology in the Industrial Revolution 4.0 era has brought significant changes in airport service management, particularly in operational safety and efficiency. One crucial component is Ground Support Equipment (GSE), which is still predominantly managed manually, resulting in ineffective supervision. This study aims to identify weaknesses in the manual GSE reporting system and to design a mobile application-based digital reporting system at BLU Office of Class I UPBU Aji Pangeran Tumenggung Pranoto Samarinda. The research employed a qualitative approach using observation, interviews, and document studies. The results indicate that the manual system leads to supervision delays, data loss potential, and low monitoring effectiveness of operational vehicles. The implementation of a mobile application equipped with QR Code features, automatic verification, notification reminders, and operational dashboards improves reporting speed, data accuracy, and real-time supervision effectiveness. The digitization of GSE reporting contributes to strengthening airside operational safety standards and has the potential for replication in other airport environments in Indonesia.